Influence of cutting height on biomass yield and quality of miscanthus genotypes. Issue 10 (26th July 2021) - Magenau, Elena; Kiesel, Andreas; Clifton‐Brown, John; Lewandowski, Iris
Abstract: Commercially achieved biomass yields are often lower than those obtained in scientific plot trials and estimated by crop models. This phenomenon is commonly referred to as the 'commercial yield gap'. It needs to be understood and managed to achieve the yield expectations that underpin business models. Cutting height at harvest is one of the key factors determining biomass yield and quality. This study quantifies the impacts of cutting heights of diverse genotypes with different morphologies and in years with contrasting weather conditions before and during harvest. Harvests were made in March 2015 and March 2018 of six diverse miscanthus genotypes planted as part of the 'OPTIMISC project' in 2013 near Stuttgart, Germany. Biomass yield, dry matter content and nutrient concentrations were analysed in four 10 cm fractions working upwards from the ground level and a fifth fraction with the shoot biomass higher than 40 cm. As stems are slightly tapered (i.e. diameter decreases slightly with increasing cutting height), it was hypothesized that low cutting may lead to yield gains, but that these may be associated with lower quality biomass with higher moisture and higher nutrient offtakes. We calculated average yield losses of 270 kg ha −1 (0.83%) with each 1 cm increase in cutting height up to 40 cm. Although whole shoot mineral concentrations were significantly influenced by both genotype and year interactions, total nitrogen (1.89 mg g −1 ), phosphorus (0.51 mg g −1 ), potassium (3.72 mg g −1 ) and calcium (0.89 mg g −1 ) concentrations did not differ significantly from the concentrations in the lower basal sections. Overall, cutting height had a limited influence on nutrient and moisture content. Therefore, we recommend that cutting is performed as low as is practically possible with the available machinery and local ground surface conditions to maximize biomass yield. Abstract : Cutting height is one of the key factors influencing the 'commercial yield gap'. This term refers to the phenomena that commercial miscanthus yields are lower than those determined in scientific trials. This study quantifies the impacts of cutting height on biomass yield and quality of miscanthus genotypes with contrasting weather conditions before and during harvest in Germany. The results indicate a yield decrease of 270 kg ha −1 with each 1 cm increase in cutting height, but only limited influence on nutrient and moisture content. Therefore, we recommend that cutting is performed as low as is practically possible to maximize biomass yield.